2018
DOI: 10.1002/2017jg004340
|View full text |Cite
|
Sign up to set email alerts
|

Water Mass Control on Phytoplankton Spatiotemporal Variations in the Northeastern East China Sea and the Western Tsushima Strait Revealed by Lipid Biomarkers

Abstract: Continental margin ecosystems in the western North Pacific Ocean are subject to strong climate forcing and anthropogenic impacts. To evaluate mechanisms controlling phytoplankton biomass and community structure variations in marginal sea‐open ocean boundary regions, brassicasterol, dinosterol, and C37 alkenones were measured in suspended particles in summer and autumn from 2012 to 2013 in the northeastern East China Sea and the western Tsushima Strait. In summer, the concentrations of brassicasterol (40–1535 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
(82 reference statements)
5
11
0
Order By: Relevance
“…Dinoflagellates (27%), cryptophytes (>20%), and haptophytes (>20%) contributed more to the total abundance in the YSBCW region, whereas diatoms accounted for ~60% in other regions, particularly affected by CDW (Figure ). This result coincided with previous studies in the SYS based on pigment signatures (Li et al, ; Liu, Huang, Huang, et al, ), lipid biomarker (Bi et al, ; Wu et al, ), and microscopic observation (Liu, Huang, Zhai, et al, ; Tian & Sun, ). However, early studies have observed higher dominance of cyanobacteria (mainly Synechococcus ) in YSBCW region than in coastal waters (Le et al, ; Li et al, ; Liu, Huang, Huang, et al, ), but the present study did not find the same result (Figure ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Dinoflagellates (27%), cryptophytes (>20%), and haptophytes (>20%) contributed more to the total abundance in the YSBCW region, whereas diatoms accounted for ~60% in other regions, particularly affected by CDW (Figure ). This result coincided with previous studies in the SYS based on pigment signatures (Li et al, ; Liu, Huang, Huang, et al, ), lipid biomarker (Bi et al, ; Wu et al, ), and microscopic observation (Liu, Huang, Zhai, et al, ; Tian & Sun, ). However, early studies have observed higher dominance of cyanobacteria (mainly Synechococcus ) in YSBCW region than in coastal waters (Le et al, ; Li et al, ; Liu, Huang, Huang, et al, ), but the present study did not find the same result (Figure ).…”
Section: Discussionsupporting
confidence: 92%
“…However, small‐celled groups (e.g., cryptophytes and coccolithophores) are dominant in the stable oligotrophic YSBCW region because of their lower nutrient requirements and higher nutrient diffusion rates (Finkel et al, ; Irwin et al, ). Such spatial variability of different taxonomic groups due to the limitation of nutrients and light was reported from previous studies in the CJE and adjacent waters (Bi et al, ; Jiang et al, ; Zhu et al, ). Similar effect of large river discharge and associated nutrients on phytoplankton community was reported in plumes of Mississippi (Chakraborty & Lohrenz, ), Amazon (Goes et al, ), and Mackenzie Rivers (Ardyna et al, ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations